2017
DOI: 10.1371/journal.pone.0186717
|View full text |Cite
|
Sign up to set email alerts
|

Methodological aspects of MRI of transplanted superparamagnetic iron oxide-labeled mesenchymal stem cells in live rat brain

Abstract: In vivo tracking of transplanted mesenchymal stem cells (MSCs) migration and homing is vital for understanding the mechanisms of beneficial effects of MSCs transplantation in animal models of diseases and in clinical trials. Transplanted cells can be labeled with superparamagnetic iron oxide (SPIO) particles and visualized in vivo using a number of iron sensitive MRI techniques. However, the applicability of those techniques for SPIO-labeled MSCs tracking in live brain has not been sufficiently investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
1
17
1
2
Order By: Relevance
“…On the other side, the non-labeled cells did not show hypointense regions similar to those observed with the labeled cells; however, there were minor magnetic field distortions along the needle and injection sites, similar to the findings of Namestnikova et al 38 and Brisset et al 39 We observed "blooming effect" which decreased with time in images acquired using T 2 * FLASH sequence for higher number of labeled cells, denoted by spread of the hypointense regions due to disturbance of the magnetic field of a region bigger than that occupied by the cells by iron nanoparticles. 38 Although the T 2 * FLASH sequence was sensitive enough to detect 2000 labeled cells, it did not show clear anatomical structures of the brain. Whereas, the T 2 MSME sequence was not as sensitive as the T 2 * FLASH sequence in detecting small numbers of labeled cells; it showed more clear anatomical structures of the brain and more realistic sizes of the transplanted cells regions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other side, the non-labeled cells did not show hypointense regions similar to those observed with the labeled cells; however, there were minor magnetic field distortions along the needle and injection sites, similar to the findings of Namestnikova et al 38 and Brisset et al 39 We observed "blooming effect" which decreased with time in images acquired using T 2 * FLASH sequence for higher number of labeled cells, denoted by spread of the hypointense regions due to disturbance of the magnetic field of a region bigger than that occupied by the cells by iron nanoparticles. 38 Although the T 2 * FLASH sequence was sensitive enough to detect 2000 labeled cells, it did not show clear anatomical structures of the brain. Whereas, the T 2 MSME sequence was not as sensitive as the T 2 * FLASH sequence in detecting small numbers of labeled cells; it showed more clear anatomical structures of the brain and more realistic sizes of the transplanted cells regions.…”
Section: Discussionsupporting
confidence: 86%
“…We found that the decay in signal is correlated to the number of labeled cells, and that the scan parameters were sensitive enough to visualize about 175 labeled cells. There are published studies that reported different limits of sensitivity of detection for lower number of cells; 19,38 however, we cannot compare their findings to ours due to any of the following factors: different magnetic field strength of MRI scanners, varying MRI sequence protocols, distinct cell types, different nanoparticle formulations, and postprocessing of images. For in vivo live imaging of mice brains, we did not use the same scan sequence protocols we used for phantoms due to long scan times which were not suitable for live animals.…”
Section: Discussioncontrasting
confidence: 64%
“…To prove the donor origin of cells observed in MRI, additional methods, i.e., bioluminescence or immunohistochemically, are used. Namestnikova et al performed the co-localization studies of iron nanoparticles conjugated with fluorescence magnetic polymers MC03F and membrane marker PKH26 [21]. Walczak et al employed the marker of proliferating cells BrdU to show MSCs infused intra-arterially in the donor tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…Этот эффект может быть обусловлен преимущественной миграцией МСК в нейрогенные зоны мозга и непосредственным взаимодействием с нейральными прогениторами реципиента, но может быть опосредован и воздействием секретируемых пересаженными МСК факторами [37]. Для понимания механизма действия трансплантированных клеток необходима разработка максимально надежных и чувствительных методов изучения их миграции и хоуминга как при жизни, так и на гистологических срезах, что в настоящее время достижимо с помощью магнитно-резонансной томографии и конфокальной микроскопии [48].…”
Section: нскunclassified
“…Однако ряд авторов [68,69] сообщили о риске развития эмболических инсультов при таком способе введения СК. Тем не менее другие исследователи [48,[70][71][72] считают, что эмболических осложнений можно избежать при подборе оптимальной дозы, скорости и условий введения СК. Доза и скорость введения являются важными пара-метрами для всех способов введения СК.…”
Section: способы трансплантацииunclassified